Calidad de servicio de saneamiento y la satisfacción del usuario de la ciudad de Iquitos 2022 - Santa Cruz Arévalo, César Antonio (2023)
The development of this thesis had the purpose of determining the relationship between the quality of sanitation service and user satisfaction in the city of Iquitos, 2022. This research was carried out with an applied approach and a non-experimental design. A sample of 384 people was drawn from a population of 479,866. This sample was interviewed with two instruments. Coming to the conclusion that the level of quality of the sanitation service in the City of Iquitos is limited, since water for human consumption almost never meets the established physical, chemical and microbiological parameters. In addition, the water sent to their homes is almost never cloudy and/or colored. On the other hand, the company usually offers detailed information on payment invoices. Satisfaction remains at a medium level, since users are not entirely satisfied with the situation, since they feel insecure about investment projects, dissatisfied with the disclosure of environmental cleanup plans, responses to complaints about damage caused and the pressure they receive from the networks to provide drinking water to homes. Finally, it was determined that there is a strong relationship between the variables studied, confirmed by a coefficient of 0.790 and a significance of 0.000.